BiOCl/TiO2/diatomite composites with enhanced visible-light photocatalytic activity for the degradation of rhodamine B - Minlin Ao (Beilstein Journal of Nanotechnology, 2019)
A BiOCl/TiO2/diatomite (BTD) composite was synthesized via a modified sol–gel method and precipitation/calcination method for application as a photocatalyst and shows promise for degradation of organic pollutants in wastewater upon visible-light irradiation. In the composite, diatomite was used as a carrier to support a layer of titanium dioxide (TiO2) nanoparticles and bismuth oxychloride (BiOCl) nanosheets. The results show that TiO2 nanoparticles and BiOCl nanosheets uniformly cover the surface of diatomite and bring TiO2 and BiOCl into close proximity. Rhodamine B was used as the target degradation product and visible light (λ > 400 nm) was used as the light source for the evaluation of the photocatalytic properties of the prepared BTD composite. The results show that the catalytic performance of the BTD composite under visible-light irradiation is much higher than that of TiO2 or BiOCl alone. When the molar ratio of BiOCl to TiO2 is 1:1 and the calcination temperature is 400 °C, the composite was found to exhibit the best catalytic effect. Through the study of the photocatalytic mechanism, it is shown that the strong visible-light photocatalytic activity of the BTD composite results mainly from the quick migration of photoelectrons from the conduction band of TiO2/diatomite to the surface of BiOCl, which promotes the separation effect and reduces the recombination rate of the photoelectron–hole pair. Due to the excellent catalytic performance, the BTD composite shows great potential for wide application in the field of sewage treatment driven by solar energy.